Radio Galaxy Zoo: Host galaxies and radio morphologies derived from visual inspection - Banfield, J.; Wong, O.; Willett, K.; Norris, R.; Rudnick, L.; Shabala, S.; Simmons, B.; Snyder, C.; Garon, A.; Seymour, Nick; Middelberg, E.; Andernach, H.; et al. (2015)
We present results from the first 12 months of operation of Radio Galaxy Zoo, which upon completion will enable visual inspection of over 170 000 radio sources to determine the host galaxy of the radio emission and the radio morphology. Radio Galaxy Zoo uses 1.4 GHz radio images from both the Faint Images of the Radio Sky at Twenty Centimeters (FIRST) and the Australia Telescope Large Area Survey (ATLAS) in combination with mid-infrared images at 3.4 μm from the Wide-field Infrared Survey Explorer (WISE) and at 3.6 μm from the Spitzer Space Telescope. We present the early analysis of the WISE mid-infrared colours of the host galaxies. For images in which there is >75 per cent consensus among the Radio Galaxy Zoo cross-identifications, the project participants are as effective as the science experts at identifying the host galaxies. The majority of the identified host galaxies reside in the mid-infrared colour space dominated by elliptical galaxies, quasi-stellar objects and luminous infrared radio galaxies. We also find a distinct population of Radio Galaxy Zoo host galaxies residing in a redder mid-infrared colour space consisting of star-forming galaxies and/or dust-enhanced non-star-forming galaxies consistent with a scenario of merger-driven active galactic nuclei (AGN) formation. The completion of the full Radio Galaxy Zoo project will measure the relative populations of these hosts as a function of radio morphology and power while providing an avenue for the identification of rare and extreme radio structures. Currently, we are investigating candidates for radio galaxies with extreme morphologies, such as giant radio galaxies, late-type host galaxies with extended radio emission and hybrid morphology radio sources.